2005
DOI: 10.1074/jbc.m408286200
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin Signaling in the Renal Collecting Duct

Abstract: Prostaglandins mediate autacrine and paracrine signaling over short distances. We used the renal collecting duct as a model system to test the hypothesis that local control of prostaglandin signaling is achieved by expressing inactivation in the same cell as synthesis. Immunocytochemical studies demonstrated that renal collecting ducts in situ express the prostaglandin (PG) synthesis enzyme, cyclooxygenase-1 (COX-1), as well as both components of prostaglandin metabolic inactivation, i.e. the prostaglandin upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Recently, specific prostaglandin transporter PGT has been cloned [16]. It has been thought that PGT takes up and oxidizes PGE 2 to the inactive metabolites, thus terminating PGE 2 actions [25]. However, our findings imply that PGE 2 take-up by PGT is the first step in novel intracellular function of PGE 2 .…”
Section: Discussionmentioning
confidence: 63%
“…Recently, specific prostaglandin transporter PGT has been cloned [16]. It has been thought that PGT takes up and oxidizes PGE 2 to the inactive metabolites, thus terminating PGE 2 actions [25]. However, our findings imply that PGE 2 take-up by PGT is the first step in novel intracellular function of PGE 2 .…”
Section: Discussionmentioning
confidence: 63%
“…The key event in preserving epithelial proliferation appears to be the achievement of high levels of PGE 2 in the pericryptal niche. PGE 2 has a short half-life and acts over short distances (34,35). Therefore, PSCs positioned closer to crypt epithelial cells should increase the local concentration of PGE 2 .…”
Section: Discussionmentioning
confidence: 99%
“…This fact was supported by a study showing its coordinate expression together with enzymes of prostaglandin synthesis (e.g. COX-1) and degradation (15-hydroxy prostaglandin dehydrogenase) in the same cells of the rat cortical collecting duct [8]. For the human gastric mucosa different studies showed the localization of COX-1 and COX-2 in parietal cells and gastric glands of human stomach under normal and certain pathological conditions [28,29].…”
Section: Discussionmentioning
confidence: 95%
“…by the expression of several prostanoid receptors (EP1-EP4). For example, rat Oatp2a1 is expressed in cells of cortical collecting duct of rat kidney [8], and human OATP2A1 is localized e.g. in the neck region and deep pyloric glands of antrum and in parietal cells of gastric corpus [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation